Phenolic Acid Profiles and Antioxidant Activity of Major Cereal Crops - Daniela Horvat; Gordana Šimić; Georg Drezner; Alojzije Lalić; Tatjana Ledenčan; Marijana Tucak; Hrvoje Plavšić; Luka Andrić; Zvonimir Zdunić (MDPI AG, 2020)
Phenolic acids (PAs) are a dominant group of phenolic compounds in cereals, existing mostly bound to compounds of cell wall. In this study, a total of 25 cereal grain samples, including wheat, winter and spring barley, corn, and popcorn, were evaluated for bound PAs and antioxidant activity in a two-year field trial. The PA contents, determined by HPLC, were significantly affected by cereal type. The mean total PA content was highest in popcorn and corn (3298 and 2213 μg/gdm, respectively), followed by winter and spring barley (991 and 908 μg/gdm, respectively) and wheat (604 μg/gdm). Ferulic acid was the most abundant, accounting from 62% to 83% of total PAs (in popcorn and winter and spring barley, respectively). Across cereals, p-coumaric (35-259 μg/gdm) and p-hidroxybenzoic (45-79 μg/gdm) were also dominant, while in corn and popcorn o-coumaric (71 and 89 μg/gdm, respectively) also occurred in higher content. The mean total phenol content ranged from 853 μg GAE/gdm (wheat) to 1403 μg GAE/gdm (winter barley) with DPPH scavenging activity from 14% to 67%, respectively. A significant influence of crop years on the ferulic acid and total PA content was found, while the variability of other PAs was dependent on the cereal type. The results indicated a high health benefit potential of selected cereals.